Assembling Defined DNA Nanostructure with Nitrogen‐Enriched Carbon Dots for Theranostic Cancer Applications. Issue 19 (17th April 2020) - Wu, Di; Li, Bang Lin; Zhao, Qianwen; Liu, Qian; Wang, Dong; He, Binfeng; Wei, Zhenghua; Leong, David Tai; Wang, Guansong; Qian, Hang
Abstract: DNA nanostructures as scaffolds for drug delivery, biosensing, and bioimaging are hindered by its vulnerability in physiological settings, less favorable of incorporating arbitrary guest molecules and other desirable functionalities. Noncanonical self‐assembly of DNA nanostructures with small molecules in an alternative system is an attractive strategy to expand their applications in multidisciplinary fields and is rarely explored. This work reports a nitrogen‐enriched carbon dots (NCDs)‐mediated DNA nanostructure self‐assembly strategy. Given the excellent photoluminescence and photodynamic properties of NCDs, the obtained DNA/NCDs nanocomplex holds great potential for bioimaging and anticancer therapy. NCDs can mediate DNA nanoprism (NP NCD ) self‐assembly isothermally at a large temperature and pH range in a magnesium‐free manner. To explore the suitability of NP NCD in potential biomedical applications, the cytotoxicity and cellular uptake efficiency of NP NCD are evaluated. NP NCD with KRAS siRNA (NP NCD K) is further conjugated for KRAS‐mutated nonsmall cell lung cancer therapy. The NP NCD K shows excellent gene knockdown efficiency and anticancer effect in vitro. The current study suggests that conjugating NCDs with programmable DNA nanostructures is a powerful strategy to endow DNA nanostructures with new functionalities, and NP NCD may be a potential theranostic platform with further fine‐tuned properties of CDs such as near‐red fluorescence or photothermal activities. Abstract : Noncanonical self‐assembly of DNA is an attractive strategy to expand their applications in multidisciplinary fields and is rarely explored. This work reports a nitrogen‐enriched carbon dots (NCDs)‐mediated DNA self‐assembly strategy. NCDs‐conjugated DNA nanostructures may be a potential theranostic platform with further fine‐tuned NCDs properties such as near‐red fluorescence or photothermal activities.